Adhesive preparation method, adhesive and lithium ion battery
By introducing aqueous organic fluorine modified acrylic acid technology into lithium-ion battery adhesives, the shortcomings of existing adhesives in terms of flexibility, solvent resistance and compatibility are solved, and higher battery cycle stability and capacity retention are achieved.
Patent Information
- Application Number
- CN202510116815.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-22
AI Technical Summary
The existing lithium-ion battery binders have shortcomings in flexibility, solvent resistance and compatibility with the PVDF layer, resulting in deterioration in battery performance during charge and discharge cycles and high temperature storage.
A water-based organic fluorine-modified acrylic binder is used to prepare a method. By using pure water as a solvent under nitrogen protection, comonomer and initiator dropwise addition, and fluorine-containing monomer and neutralizing agent are introduced during the reaction, the pH value is adjusted to improve the performance of the binder.
It significantly improves the solvent resistance, flexibility and compatibility with the PVDF layer of the adhesive, improves the cycle stability and capacity retention of the battery, and is suitable for high-performance lithium-ion batteries.
Smart Images

Figure CN119859494A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water-based adhesives, and more specifically, to an adhesive preparation method, an adhesive and a lithium-ion battery. Background Art
[0002] At present, the commonly used binders in the lithium-ion battery industry mainly include polyvinylidene fluoride (PVDF), styrene-butadiene rubber latex and carboxymethyl cellulose (SBR / CMC) and polyacrylic acid (PAA).
[0003] PVDF binder has good adhesion to aluminum foil and strong resistance to electrochemical corrosion. However, PVDF has poor adhesion to copper foil. In addition, it has a large molecular weight and no hydrophilic groups, so N-methylpyrrolidone (NMP) is required as a solvent when dispersing and dissolving PVDF. NMP is sensitive to moisture, highly toxic, and volatile, and is prone to environmental pollution. In addition, the price of PVDF binder is relatively high.
[0004] In SBR / CMC binders, carboxymethyl cellulose (CMC) has average viscosity, high brittleness, and poor flexibility, which makes the electrode plates prone to cracking during the charge and discharge process. At the same time, styrene-butadiene rubber (SBR) swells greatly in the electrolyte, especially when applied to graphite negative electrodes and silicon-based new negative electrodes based on the point-to-point bonding mechanism. Due to the repeated expansion and contraction of the volume of the graphite negative electrode and the silicon-based negative electrode during the charge and discharge cycle, the binder easily loses its adhesion, resulting in capacity loss, especially the degradation of high-temperature storage and high-temperature cycle performance.
[0005] Polyacrylic acid (PAA) binders have excellent performance in terms of bonding strength, stability, price and environmental protection, and have become a hot research topic for negative electrode binders. However, ordinary PAA binders may become hard and brittle after drying the solvent, which does not meet the flexibility requirements of the negative electrode.
[0006] Among the positive electrode active layer binders, polyvinylidene fluoride (PVDF) still occupies a dominant position. PAA is usually used as a connecting layer binder to provide adhesion to the aluminum foil layer and the PVDF layer. Although the PAA binder on the market can bond well to the aluminum foil layer, its adhesion to the PVDF layer is slightly poor. Therefore, the PAA binder needs to be modified to simultaneously meet the requirements for adhesion, solvent resistance and flexibility.
[0007] At present, there are copolymerized PAA solution products being developed. Most of these products are based on acrylic acid, and are obtained through copolymerization modification of acrylamide, acrylonitrile and acrylate to obtain multi-component copolymers. The copolymers produced by this route have great defects, such as hard and brittle materials, poor dispersion performance, and improved adhesion to the PVDF layer, but still insufficient. Summary of the invention
[0008] In order to overcome the technical problems existing in the above prior art, the present invention provides a method for preparing an adhesive, an adhesive and a lithium ion battery.
[0009] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0010] A method for preparing an adhesive, the method comprising the following steps, measured in parts by weight:
[0011] Under nitrogen protection, 60-80 parts of pure water as solvent are added into the reactor;
[0012] 0.1-0.3 parts of initiator and 5-15 parts of pure water are mixed to prepare solution A, and i types of comonomers are mixed to prepare solution B, where i≥1;
[0013] The temperature of the reaction kettle is adjusted to 35-95° C., and the solution A and the solution B are dripped into the reaction kettle within 1-4 hours;
[0014] After the solution A and the solution B are added dropwise, the reactor is kept warm. After 1-4 hours of warming, the temperature of the reactor is adjusted to 50-90° C., and 0-5 parts of fluorine-containing monomer are added to react;
[0015] After adding the fluorine-containing monomer and reacting for 1-3 hours, the temperature of the reactor is adjusted to 35-65° C., 0.1-0.3 parts of a neutralizing agent are added, and after neutralization for 0.5-1 hour, the reaction mixture is cooled to obtain a water-based organic fluorine-modified acrylic adhesive.
[0016] This adhesive preparation method covers the complete process from raw material selection to final product. By reacting under nitrogen protection, it effectively avoids the interference of oxygen in the air on the polymerization reaction, and improves the stability and yield of the reaction. Using pure water as a solvent is not only environmentally friendly, but also reduces the use of toxic solvents, which is in line with the concept of sustainable development. The diversified selection of comonomers allows adhesives with different performance characteristics to be obtained by adjusting different monomer ratios, thereby meeting the needs of different application scenarios. The precise control of the reaction temperature and the reasonable design of the drop time ensure the uniformity and efficiency of the reaction, and further improve the performance of the adhesive. The addition of fluorinated monomers for modification significantly improves the solvent resistance and interfacial wettability of the adhesive, and enhances its compatibility with the PVDF layer. The addition of a neutralizer adjusts the pH value of the product, making it more stable and suitable for subsequent processing and application. Overall, the adhesive prepared by this method not only has excellent performance, but also has an environmentally friendly and highly controllable production process, and has a high industrial application value.
[0017] Furthermore, the initiator is at least one of ammonium persulfate, potassium persulfate, sodium bisulfite, sodium hypophosphite, azobisisobutylimidazoline hydrochloride, and azobisisobutylamidine hydrochloride.
[0018] The above examples illustrate the types of initiators, among which ammonium persulfate and potassium persulfate are water-soluble initiators that can quickly initiate free radical polymerization reactions in aqueous systems, thereby increasing the reaction rate and yield. Sodium bisulfite and sodium hypophosphite are mild initiators, suitable for systems with high requirements for reaction conditions, and can reduce the occurrence of side reactions. Azobisisobutylimidazoline hydrochloride and azobisisosoyamidine hydrochloride are organic initiators with high initiation efficiency and selectivity. They can initiate polymerization reactions at lower temperatures and are suitable for temperature-sensitive materials. The selection of these initiators not only ensures the smooth progress of the polymerization reaction, but also allows the type of initiator to be flexibly adjusted according to specific application scenarios and requirements, thereby optimizing the performance of the adhesive. In addition, the use of multiple initiators also improves the stability and reliability of the reaction and reduces the potential risks caused by a single initiator.
[0019] Furthermore, the comonomer is at least one of acrylic acid, methacrylic acid, itaconic acid, diethyl itaconate, acrylonitrile, methacrylonitrile, acrylamide, and methacrylamide.
[0020] The above examples illustrate the types of comonomers. Among them, acrylic acid and methacrylic acid have strong acidity and can provide abundant carboxyl functional groups. These functional groups not only enhance the adhesion of the adhesive, but also provide grafting sites for it, which is conducive to the introduction of fluorinated monomers. Itaconic acid and diethyl itaconate can provide additional double bonds, increase the crosslinking degree of the polymer, and improve the mechanical strength and stability of the adhesive. Acrylonitrile and methacrylonitrile have high heat resistance and solvent resistance, which can enhance the overall performance of the adhesive. Acrylamide and methacrylamide provide amino functional groups, which can form hydrogen bonds with electrode materials to further improve adhesion and interfacial stability. By rationally selecting and matching these comonomers, adhesives with a variety of excellent properties can be prepared to meet the high requirements of lithium batteries for adhesives. In addition, this diversity also makes it possible to flexibly adjust the types and proportions of comonomers according to the characteristics of different electrode materials to achieve optimal matching and performance optimization.
[0021] Furthermore, the structure of the fluorine-containing monomer is:
[0022]
[0023] Among them, 3≤n≤6, 6≤m≤8.
[0024] The above examples illustrate the structure of fluorinated monomers, where n = 3 to 6, m = 6 to 8; fluorinated monomers of this structure have a good balance of hydrophilicity and hydrophobicity, and can effectively improve the dispersibility and flexibility of the adhesive. The long-chain polyethylene glycol portion increases the flexibility and ductility of the adhesive, allowing it to better adapt to the volume changes of the electrode material during the charge and discharge process, reduce cracking and peeling, and improve the cycle stability and capacity retention rate of the battery. At the same time, the introduction of the fluorinated portion improves the solvent resistance and interfacial wettability of the adhesive, making it less likely to swell in the electrolyte and maintain good mechanical properties and electrochemical stability. The structural design of this fluorinated monomer not only solves the deficiencies of traditional PAA adhesives in flexibility and solvent resistance, but also greatly improves the compatibility of the adhesive with the PVDF layer, so that it exhibits excellent bonding properties in both the positive and negative electrodes. Overall, the structural design of this fluorinated monomer provides an important technical basis for the preparation of high-performance lithium battery adhesives, with significant innovation and application prospects.
[0025] Furthermore, the neutralizing agent is at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, triethylamine, ammonia water, N,N-dialkylethanolamine, and N,N-dialkylhydroxylamine.
[0026] The above examples illustrate the types of neutralizers. The use of these neutralizers can effectively adjust the pH value of the polymer, making it more stable in a neutral or weakly alkaline environment. Inorganic bases such as lithium hydroxide, sodium hydroxide, and potassium hydroxide not only have good neutralization effects, but are also easy to control and can quickly adjust the pH value of the solution. Calcium hydroxide has low water solubility and is suitable for systems that require long-term stability. Carbonates such as lithium carbonate, sodium carbonate, and potassium carbonate can provide neutralization while also having a certain buffering capacity, which helps to maintain the pH value of the reaction system stable. Organic neutralizers such as triethylamine and ammonia water have low alkalinity and can be slowly released under specific conditions, avoiding the unevenness caused by too fast neutralization reaction. Multifunctional neutralizers such as N,N-dialkylethanolamine and N,N-dialkylhydroxylamine can not only adjust the pH value, but also form chemical bonds with carboxyl or amino groups in the polymer, further improving the stability and adhesion of the adhesive. This diverse selection of neutralizers allows the most suitable neutralizer to be flexibly selected according to specific application scenarios and needs, ensuring that the prepared adhesive has the best performance and stability. In addition, the rational selection of neutralizers can also improve the processing properties of adhesives, making them easier to use in actual production.
[0027] Further, the step of dripping the solution A and the solution B into the reaction kettle within 1-4 hours is specifically as follows:
[0028] The solution A and the solution B are respectively dripped into the reaction kettle at a uniform speed within 1-4 hours.
[0029] Here, the dripping method of solution A and solution B is further limited, that is, they are uniformly dripped into the reactor within 1-4 hours. This uniform dripping method can ensure that the initiator and the comonomer are uniformly distributed in the reaction system, avoiding the situation of local over-concentration or over-dilute, thereby improving the uniformity and controllability of the polymerization reaction. Uniform reaction conditions are conducive to the formation of polymers with narrow molecular weight distribution and stable performance, further improving the overall performance of the adhesive. In addition, uniform dripping can also effectively control the reaction rate, prevent the temperature runaway and the occurrence of side reactions caused by too fast reaction, and ensure the safety and stability of the reaction. In actual production, this control method can simplify the operating steps, improve production efficiency, reduce production costs, and has high industrial application value.
[0030] Furthermore, the adhesive preparation method is specifically as follows:
[0031] Under nitrogen protection, 70 parts of pure water were added into the reactor as a solvent;
[0032] 0.15 parts of an initiator and 10 parts of pure water are mixed to form a solution A, wherein the initiator is ammonium persulfate; three comonomers are mixed to form a solution B, wherein the three comonomers include 18 parts of acrylic acid, 3 parts of acrylonitrile and 2 parts of acrylamide;
[0033] After the temperature of the reactor reaches 90° C., the solution A is evenly dripped into the reactor within 3 hours, and the solution B is evenly dripped into the reactor within 2 hours;
[0034] After the solution A and the solution B are added dropwise, the reactor is kept warm. After 2 hours of warming, the temperature of the reactor is adjusted to 70° C., and 1 portion of fluorinated monomer is added to react;
[0035] After adding the fluorine-containing monomer and reacting for 2 hours, the temperature of the reactor was adjusted to 60° C., 0.2 parts of a neutralizing agent was added, and the neutralizing agent was sodium hydroxide. After neutralization for 0.5 hours, the mixture was cooled to obtain a water-based organic fluorine-modified acrylic adhesive.
[0036] A specific embodiment is provided above, which describes the preparation process of the adhesive in detail. Using 70 parts of pure water as a solvent is not only environmentally friendly, but also ensures the stability and uniformity of the reaction system. Ammonium persulfate is used as an initiator, which has high initiation efficiency and applicability, and can effectively promote the polymerization reaction. Acrylic acid, acrylonitrile and acrylamide are selected as comonomers. By adjusting their proportions, the bonding force, mechanical strength and flexibility of the adhesive can be improved at the same time. The gradual adjustment of the reaction temperature and the heat preservation treatment ensure the full progress of the polymerization reaction and the uniform distribution of the product. The introduction of fluorine-containing monomers further improves the solvent resistance and interfacial wettability of the adhesive, making it outstanding in bonding with the PVDF layer. Finally, sodium hydroxide is used as a neutralizing agent, and the pH value can be quickly adjusted to make the performance of the adhesive more stable. Through this specific preparation method, a water-based organic fluorine-modified acrylic adhesive with excellent comprehensive performance can be obtained, which is suitable for the application of high-performance lithium batteries and has high practical value and market prospects.
[0037] Furthermore, the adhesive preparation method is specifically as follows:
[0038] Under nitrogen protection, 70 parts of pure water were added into the reactor as a solvent;
[0039] 0.15 parts of an initiator and 10 parts of pure water are mixed to form a solution A, wherein the initiator is ammonium persulfate; five comonomers are mixed to form a solution B, wherein the five comonomers include 15 parts of acrylic acid, 3 parts of acrylonitrile, 2 parts of acrylamide, 1 part of itaconic acid and 2 parts of diethyl itaconate;
[0040] After the temperature of the reactor reaches 90° C., the solution A is evenly dripped into the reactor within 3 hours, and the solution B is evenly dripped into the reactor within 2 hours;
[0041] After the solution A and the solution B are added dropwise, the reactor is kept warm. After 2 hours of warming, the temperature of the reactor is adjusted to 70° C., and 1 portion of fluorinated monomer is added to react;
[0042] After adding the fluorine-containing monomer and reacting for 2 hours, the temperature of the reactor was adjusted to 60° C., 0.2 parts of a neutralizing agent was added, and the neutralizing agent was sodium hydroxide. After neutralization for 0.5 hours, the mixture was cooled to obtain a water-based organic fluorine-modified acrylic adhesive.
[0043] Another specific embodiment is provided above, and the preparation process of the adhesive is described in detail. By introducing itaconic acid and diethyl itaconate, the crosslinking degree of the polymer is increased, thereby improving the mechanical strength and stability of the adhesive. These two monomers can also provide additional carboxyl groups and double bonds, which are conducive to the grafting reaction of fluorine-containing monomers, and further enhance the solvent resistance and interfacial wettability of the adhesive. At the same time, the introduction of itaconic acid and diethyl itaconate makes the adhesive show better thermal stability at high temperatures, reducing the performance degradation during high temperature storage and high temperature circulation. Ammonium persulfate, as an initiator, can effectively promote the polymerization reaction and improve the reaction rate and yield. The addition of acrylic acid, acrylonitrile and acrylamide ensures the basic properties of the adhesive, such as bonding strength and flexibility. The gradual adjustment of the reaction temperature and the heat preservation treatment make the reaction more uniform and controllable, ensuring the molecular weight distribution and stable performance of the polymer. Finally, sodium hydroxide is used as a neutralizing agent, and the pH value can be quickly adjusted to make the performance of the adhesive more stable. Through this specific preparation method, a water-based organic fluorine-modified acrylic adhesive with better comprehensive performance can be obtained, which has higher adhesion, better solvent resistance and better flexibility, and is suitable for the application of high-performance lithium batteries.
[0044] An adhesive is a water-based organic fluorine-modified acrylic adhesive prepared by the above-mentioned adhesive preparation method.
[0045] Through the above preparation method, an adhesive with excellent bonding force, solvent resistance and flexibility can be obtained. This adhesive is not only environmentally friendly, but also has stable performance, and can show good application effects in various battery systems. In particular, in terms of stability under high temperature environment and compatibility with PVDF layer, the adhesive has significant advantages and can effectively improve the cycle performance and capacity retention rate of the battery. In addition, the preparation method of this adhesive is simple and highly controllable, suitable for large-scale industrial production, and has high economy and market competitiveness. In general, this adhesive product fills the gap of high-performance, environmentally friendly adhesives on the market, and has important technical significance and commercial value.
[0046] A lithium ion battery comprises the aforementioned adhesive.
[0047] The introduction of this adhesive significantly improves the overall performance of the battery. First, due to the excellent bonding force of the adhesive, it can effectively improve the adhesion and stability of the electrode material, reduce the shedding and cracking of the electrode material during the charging and discharging process, thereby improving the cycle life and capacity retention rate of the battery. Secondly, the solvent resistance of the adhesive makes it difficult to swell in the electrolyte, maintain good mechanical properties and electrochemical stability, and further improve the reliability and safety of the battery. In addition, the flexibility of the adhesive enables it to better adapt to the volume change of the electrode material during the charging and discharging process, reduce the damage caused by internal stress, and improve the overall structural stability of the electrode. The introduction of fluorinated monomers also enhances the compatibility of the adhesive with the PVDF layer, so that both the positive and negative electrode materials can obtain a good bonding effect. In general, this lithium-ion battery is not only superior to traditional batteries in performance, but also meets the requirements of environmental protection and sustainable development, and has important technical significance and market prospects. By using this high-performance adhesive, the overall performance and service life of lithium-ion batteries can be effectively improved to meet the needs of different applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0049] Figure 1 It is a flow chart of a method for preparing an adhesive provided in one embodiment of the present application. DETAILED DESCRIPTION
[0050] In the following description, a large number of specific details are provided to provide a more thorough understanding of the present application. However, it is apparent to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features well known in the art are not described.
[0051] It should be understood that the present application can be implemented in different forms and should not be interpreted as being limited to the embodiments set forth herein. On the contrary, providing these embodiments will make the disclosure thorough and complete, and will fully convey the scope of the present application to those skilled in the art.
[0052] In order to thoroughly understand the present application, a detailed structure will be presented in the following description to illustrate the technical solution proposed by the present application. The preferred embodiments of the present application are described in detail as follows, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0053] First, as Figure 1 As shown, the present invention provides a technical solution:
[0054] A method for preparing an adhesive, the method comprising the following steps, measured in parts by weight:
[0055] Under nitrogen protection, 60-80 parts of pure water as solvent are added into the reactor;
[0056] 0.1-0.3 parts of initiator and 5-15 parts of pure water are mixed to prepare solution A, and i types of comonomers are mixed to prepare solution B, where i≥1;
[0057] The temperature of the reaction kettle is adjusted to 35-95° C., and the solution A and the solution B are dripped into the reaction kettle within 1-4 hours;
[0058] After the solution A and the solution B are added dropwise, the reactor is kept warm. After 1-4 hours of warming, the temperature of the reactor is adjusted to 50-90° C., and 0-5 parts of fluorine-containing monomer are added to react;
[0059] After adding the fluorine-containing monomer and reacting for 1-3 hours, the temperature of the reactor is adjusted to 35-65° C., 0.1-0.3 parts of a neutralizing agent are added, and after neutralization for 0.5-1 hour, the reaction mixture is cooled to obtain a water-based organic fluorine-modified acrylic adhesive.
[0060] This adhesive preparation method covers the complete process from raw material selection to final product. By reacting under nitrogen protection, it effectively avoids the interference of oxygen in the air on the polymerization reaction, and improves the stability and yield of the reaction. Using pure water as a solvent is not only environmentally friendly, but also reduces the use of toxic solvents, which is in line with the concept of sustainable development. The diversified selection of comonomers allows adhesives with different performance characteristics to be obtained by adjusting different monomer ratios, thereby meeting the needs of different application scenarios. The precise control of the reaction temperature and the reasonable design of the drop time ensure the uniformity and efficiency of the reaction, and further improve the performance of the adhesive. The addition of fluorinated monomers for modification significantly improves the solvent resistance and interfacial wettability of the adhesive, and enhances its compatibility with the PVDF layer. The addition of a neutralizer adjusts the pH value of the product, making it more stable and suitable for subsequent processing and application. Overall, the adhesive prepared by this method not only has excellent performance, but also has an environmentally friendly and highly controllable production process, and has a high industrial application value.
[0061] Furthermore, the initiator is at least one of ammonium persulfate, potassium persulfate, sodium bisulfite, sodium hypophosphite, azobisisobutylimidazoline hydrochloride, and azobisisobutylamidine hydrochloride.
[0062] The above examples illustrate the types of initiators, among which ammonium persulfate and potassium persulfate are water-soluble initiators that can quickly initiate free radical polymerization reactions in aqueous systems, thereby increasing the reaction rate and yield. Sodium bisulfite and sodium hypophosphite are mild initiators, suitable for systems with high requirements for reaction conditions, and can reduce the occurrence of side reactions. Azobisisobutylimidazoline hydrochloride and azobisisosoyamidine hydrochloride are organic initiators with high initiation efficiency and selectivity. They can initiate polymerization reactions at lower temperatures and are suitable for temperature-sensitive materials. The selection of these initiators not only ensures the smooth progress of the polymerization reaction, but also allows the type of initiator to be flexibly adjusted according to specific application scenarios and requirements, thereby optimizing the performance of the adhesive. In addition, the use of multiple initiators also improves the stability and reliability of the reaction and reduces the potential risks caused by a single initiator.
[0063] Furthermore, the comonomer is at least one of acrylic acid, methacrylic acid, itaconic acid, diethyl itaconate, acrylonitrile, methacrylonitrile, acrylamide, and methacrylamide.
[0064] The above examples illustrate the types of comonomers. Among them, acrylic acid and methacrylic acid have strong acidity and can provide abundant carboxyl functional groups. These functional groups not only enhance the adhesion of the adhesive, but also provide grafting sites for it, which is conducive to the introduction of fluorinated monomers. Itaconic acid and diethyl itaconate can provide additional double bonds, increase the crosslinking degree of the polymer, and improve the mechanical strength and stability of the adhesive. Acrylonitrile and methacrylonitrile have high heat resistance and solvent resistance, which can enhance the overall performance of the adhesive. Acrylamide and methacrylamide provide amino functional groups, which can form hydrogen bonds with electrode materials to further improve adhesion and interfacial stability. By rationally selecting and matching these comonomers, adhesives with a variety of excellent properties can be prepared to meet the high requirements of lithium batteries for adhesives. In addition, this diversity also makes it possible to flexibly adjust the types and proportions of comonomers according to the characteristics of different electrode materials to achieve optimal matching and performance optimization.
[0065] Furthermore, the structure of the fluorine-containing monomer is:
[0066]
[0067] Among them, 3≤n≤6, 6≤m≤8.
[0068] The above examples illustrate the structure of fluorinated monomers, where n = 3 to 6, m = 6 to 8; fluorinated monomers of this structure have a good balance of hydrophilicity and hydrophobicity, and can effectively improve the dispersibility and flexibility of the adhesive. The long-chain polyethylene glycol portion increases the flexibility and ductility of the adhesive, allowing it to better adapt to the volume changes of the electrode material during the charge and discharge process, reduce cracking and peeling, and improve the cycle stability and capacity retention rate of the battery. At the same time, the introduction of the fluorinated portion improves the solvent resistance and interfacial wettability of the adhesive, making it less likely to swell in the electrolyte and maintain good mechanical properties and electrochemical stability. The structural design of this fluorinated monomer not only solves the deficiencies of traditional PAA adhesives in flexibility and solvent resistance, but also greatly improves the compatibility of the adhesive with the PVDF layer, so that it exhibits excellent bonding properties in both the positive and negative electrodes. Overall, the structural design of this fluorinated monomer provides an important technical basis for the preparation of high-performance lithium battery adhesives, with significant innovation and application prospects.
[0069] Furthermore, the neutralizing agent is at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, triethylamine, ammonia water, N,N-dialkylethanolamine, and N,N-dialkylhydroxylamine.
[0070] The above examples illustrate the types of neutralizers. The use of these neutralizers can effectively adjust the pH value of the polymer, making it more stable in a neutral or weakly alkaline environment. Inorganic bases such as lithium hydroxide, sodium hydroxide, and potassium hydroxide not only have good neutralization effects, but are also easy to control and can quickly adjust the pH value of the solution. Calcium hydroxide has low water solubility and is suitable for systems that require long-term stability. Carbonates such as lithium carbonate, sodium carbonate, and potassium carbonate can provide neutralization while also having a certain buffering capacity, which helps to maintain the pH value of the reaction system stable. Organic neutralizers such as triethylamine and ammonia water have low alkalinity and can be slowly released under specific conditions, avoiding the unevenness caused by too fast neutralization reaction. Multifunctional neutralizers such as N,N-dialkylethanolamine and N,N-dialkylhydroxylamine can not only adjust the pH value, but also form chemical bonds with carboxyl or amino groups in the polymer, further improving the stability and adhesion of the adhesive. This diverse selection of neutralizers allows the most suitable neutralizer to be flexibly selected according to specific application scenarios and needs, ensuring that the prepared adhesive has the best performance and stability. In addition, the rational selection of neutralizers can also improve the processing properties of adhesives, making them easier to use in actual production.
[0071] Further, the step of dripping the solution A and the solution B into the reaction kettle within 1-4 hours is specifically as follows:
[0072] The solution A and the solution B are respectively dripped into the reaction kettle at a uniform speed within 1-4 hours.
[0073] Here, the dripping method of solution A and solution B is further limited, that is, they are uniformly dripped into the reactor within 1-4 hours. This uniform dripping method can ensure that the initiator and the comonomer are uniformly distributed in the reaction system, avoiding the situation of local over-concentration or over-dilute, thereby improving the uniformity and controllability of the polymerization reaction. Uniform reaction conditions are conducive to the formation of polymers with narrow molecular weight distribution and stable performance, further improving the overall performance of the adhesive. In addition, uniform dripping can also effectively control the reaction rate, prevent the temperature runaway and the occurrence of side reactions caused by too fast reaction, and ensure the safety and stability of the reaction. In actual production, this control method can simplify the operating steps, improve production efficiency, reduce production costs, and has high industrial application value.
[0074] Furthermore, the adhesive preparation method is specifically as follows:
[0075] Under nitrogen protection, 70 parts of pure water were added into the reactor as a solvent;
[0076] 0.15 parts of an initiator and 10 parts of pure water are mixed to form a solution A, wherein the initiator is ammonium persulfate; three comonomers are mixed to form a solution B, wherein the three comonomers include 18 parts of acrylic acid, 3 parts of acrylonitrile and 2 parts of acrylamide;
[0077] After the temperature of the reactor reaches 90° C., the solution A is evenly dripped into the reactor within 3 hours, and the solution B is evenly dripped into the reactor within 2 hours;
[0078] After the solution A and the solution B are added dropwise, the reactor is kept warm. After 2 hours of warming, the temperature of the reactor is adjusted to 70° C., and 1 portion of fluorinated monomer is added to react;
[0079] After adding the fluorine-containing monomer and reacting for 2 hours, the temperature of the reactor was adjusted to 60° C., 0.2 parts of a neutralizing agent was added, and the neutralizing agent was sodium hydroxide. After neutralization for 0.5 hours, the mixture was cooled to obtain a water-based organic fluorine-modified acrylic adhesive.
[0080] The above is a detailed preparation process of an adhesive. Using 70 parts of pure water as a solvent is not only environmentally friendly, but also ensures the stability and uniformity of the reaction system. Ammonium persulfate is used as an initiator, which has high initiation efficiency and applicability, and can effectively promote the polymerization reaction. Acrylic acid, acrylonitrile and acrylamide are selected as comonomers. By adjusting their proportions, the adhesion, mechanical strength and flexibility of the adhesive can be improved at the same time. The gradual adjustment of the reaction temperature and the heat preservation treatment ensure the full progress of the polymerization reaction and the uniform distribution of the product. The introduction of fluorine-containing monomers further improves the solvent resistance and interfacial wettability of the adhesive, making it perform well in bonding with the PVDF layer. Finally, sodium hydroxide is used as a neutralizer to quickly adjust the pH value, making the performance of the adhesive more stable. Through this specific preparation method, a water-based organic fluorine-modified acrylic adhesive with excellent comprehensive performance can be obtained, which is suitable for the application of high-performance lithium batteries and has high practical value and market prospects.
[0081] Furthermore, the adhesive preparation method is specifically as follows:
[0082] Under nitrogen protection, 70 parts of pure water were added into the reactor as a solvent;
[0083] 0.15 parts of an initiator and 10 parts of pure water are mixed to form a solution A, wherein the initiator is ammonium persulfate; five comonomers are mixed to form a solution B, wherein the five comonomers include 15 parts of acrylic acid, 3 parts of acrylonitrile, 2 parts of acrylamide, 1 part of itaconic acid and 2 parts of diethyl itaconate;
[0084] After the temperature of the reactor reaches 90° C., the solution A is evenly dripped into the reactor within 3 hours, and the solution B is evenly dripped into the reactor within 2 hours;
[0085] After the solution A and the solution B are added dropwise, the reactor is kept warm. After 2 hours of warming, the temperature of the reactor is adjusted to 70° C., and 1 portion of fluorinated monomer is added to react;
[0086] After adding the fluorine-containing monomer and reacting for 2 hours, the temperature of the reactor was adjusted to 60° C., 0.2 parts of a neutralizing agent was added, and the neutralizing agent was sodium hydroxide. After neutralization for 0.5 hours, the mixture was cooled to obtain a water-based organic fluorine-modified acrylic adhesive.
[0087] The above is another detailed preparation process of the adhesive. By introducing itaconic acid and diethyl itaconate, the crosslinking degree of the polymer is increased, thereby improving the mechanical strength and stability of the adhesive. These two monomers can also provide additional carboxyl groups and double bonds, which are beneficial to the grafting reaction of fluorinated monomers, further enhancing the solvent resistance and interfacial wettability of the adhesive. At the same time, the introduction of itaconic acid and diethyl itaconate makes the adhesive show better thermal stability at high temperatures, reducing the performance degradation during high-temperature storage and high-temperature cycling. Ammonium persulfate, as an initiator, can effectively promote the polymerization reaction and increase the reaction rate and yield. The addition of acrylic acid, acrylonitrile and acrylamide ensures the basic properties of the adhesive, such as adhesion and flexibility. The gradual adjustment of the reaction temperature and the heat preservation treatment make the reaction more uniform and controllable, ensuring the molecular weight distribution and stable performance of the polymer. Finally, sodium hydroxide is used as a neutralizer to quickly adjust the pH value and make the performance of the adhesive more stable. Through this specific preparation method, a water-based organic fluorine-modified acrylic adhesive with better comprehensive performance can be obtained, which has higher adhesion, better solvent resistance and better flexibility, and is suitable for the application of high-performance lithium batteries.
[0088] In general, acrylonitrile and acrylamide in the present invention can provide basic structural strength for the adhesive and ensure the adhesive force of the adhesive; acrylic acid, itaconic acid and acrylamide can provide grafting sites (-COOH and -NH2), so that fluorinated polyethylene glycol can be smoothly grafted on the copolymer. The long chain of polyethylene glycol can improve the flexibility and dispersibility of the prepolymer; the introduction of organic fluorine can improve the solvent resistance and interface wettability of the adhesive, and at the same time, the compatibility is better when used with the PVDF layer.
[0089] In a second aspect, the present invention provides a technical solution:
[0090] An adhesive is a water-based organic fluorine-modified acrylic adhesive prepared by the above-mentioned adhesive preparation method.
[0091] Through the above preparation method, an adhesive with excellent bonding force, solvent resistance and flexibility can be obtained. This adhesive is not only environmentally friendly, but also has stable performance, and can show good application effects in various battery systems. In particular, in terms of stability under high temperature environment and compatibility with PVDF layer, the adhesive has significant advantages and can effectively improve the cycle performance and capacity retention rate of the battery. In addition, the preparation method of this adhesive is simple and highly controllable, suitable for large-scale industrial production, and has high economy and market competitiveness. In general, this adhesive product fills the gap of high-performance, environmentally friendly adhesives on the market, and has important technical significance and commercial value.
[0092] In a third aspect, the present invention provides a technical solution:
[0093] A lithium ion battery comprises the aforementioned adhesive.
[0094] The introduction of this adhesive significantly improves the overall performance of the battery. First, due to the excellent bonding force of the adhesive, it can effectively improve the adhesion and stability of the electrode material, reduce the shedding and cracking of the electrode material during the charging and discharging process, thereby improving the cycle life and capacity retention rate of the battery. Secondly, the solvent resistance of the adhesive makes it difficult to swell in the electrolyte, maintain good mechanical properties and electrochemical stability, and further improve the reliability and safety of the battery. In addition, the flexibility of the adhesive enables it to better adapt to the volume change of the electrode material during the charging and discharging process, reduce the damage caused by internal stress, and improve the overall structural stability of the electrode. The introduction of fluorinated monomers also enhances the compatibility of the adhesive with the PVDF layer, so that both the positive and negative electrode materials can obtain a good bonding effect. In general, this lithium-ion battery is not only superior to traditional batteries in performance, but also meets the requirements of environmental protection and sustainable development, and has important technical significance and market prospects. By using this high-performance adhesive, the overall performance and service life of lithium-ion batteries can be effectively improved to meet the needs of different applications.
[0095] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be understood by those skilled in the art that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In the embodiments, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used, unless otherwise specified, can all be obtained from commercial sources.
[0096] Embodiment 1:
[0097] This embodiment provides a method for preparing an adhesive, which comprises the following steps, measured in parts by weight:
[0098] Step 1, under nitrogen protection, 70 parts of pure water as a solvent are put into a reaction kettle;
[0099] Step 2, 0.15 parts of ammonium persulfate and 10 parts of pure water were mixed to prepare solution A;
[0100] Step 3, 18 parts of acrylic acid, 3 parts of acrylonitrile, and 2 parts of acrylamide are mixed to prepare solution B;
[0101] Step 4: After reaching 90°C, solution A was evenly added to the reactor over 3 hours, and solution B was evenly added to the reactor over 2 hours;
[0102] Step 5: After the addition is completed, keep the temperature at 70°C for 2 hours and add 1 part of the grafting monomer (fluorinated monomer).
[0103]
[0104] Step 6: After reacting for 1-3 hours, adjust the temperature to 60° C., add 0.2 parts of sodium hydroxide, neutralize for 0.5 hours, and then cool to obtain a water-based organic fluorine-modified acrylic adhesive.
[0105] The viscosity is measured according to GB / T2794-2022 and is 2350 mpa.s. The non-volatile matter content is measured according to GB / T2793-1995 and is 23.58%.
[0106] Embodiment 2:
[0107] The acrylic acid ester water-based adhesive was prepared in the same manner as in Example 1, except that:
[0108] Solution B in step 3 is adjusted to 15 parts of acrylic acid, 3 parts of acrylonitrile, 2 parts of acrylamide, 1 part of itaconic acid, and 2 parts of diethyl itaconate to prepare solution B;
[0109] The viscosity is measured according to GB / T2794-2022 and is 2630 mpa.s. The non-volatile matter content is measured according to GB / T2793-1995 and is 23.7%.
[0110] Embodiment 3:
[0111] The acrylic acid ester water-based adhesive was prepared in the same manner as in Example 1, except that:
[0112] The initiator in step 2 was adjusted to azobisisobutyramidine hydrochloride.
[0113] The viscosity is measured according to GB / T2794-2022 and is 2280 mpa.s. The non-volatile matter content is measured according to GB / T2793-1995 and is 23.42%.
[0114] Embodiment 4:
[0115] The acrylic acid ester water-based adhesive was prepared in the same manner as in Example 1, except that:
[0116] Adjust the grafting monomer in step 5 to
[0117] The viscosity is measured according to GB / T2794-2022 and the non-volatile matter content is measured according to GB / T2793-1995 and is 23.69%.
[0118] Embodiment 5:
[0119] The acrylic acid ester water-based adhesive was prepared in the same manner as in Example 1, except that:
[0120] The neutralizing agent in step 6 is adjusted to lithium hydroxide.
[0121] The viscosity is measured according to GB / T2794-2022 and the non-volatile matter content is measured according to GB / T2793-1995 and is 23.52%.
[0122] Embodiment 6:
[0123] The acrylic acid ester water-based adhesive was prepared in the same manner as in Example 1, except that:
[0124] The neutralizing agent in step 6 was adjusted to N,N-dimethylethanolamine.
[0125] The viscosity is measured according to GB / T2794-2022 and the non-volatile matter content is measured according to GB / T2793-1995 and is 23.52%.
[0126] Embodiment 7:
[0127] The acrylic acid ester water-based adhesive was prepared in the same manner as in Example 1, except that:
[0128] Adjust the 1 part of grafting monomer in step 5 to 2 parts.
[0129] The viscosity is measured according to GB / T2794-2022 and the non-volatile matter content is measured according to GB / T2793-1995 and is 23.93%.
[0130] Comparative Example 1:
[0131] The acrylic acid ester water-based adhesive was prepared in the same manner as in Example 1, except that:
[0132] The grafting monomer in step 5 is adjusted to dodecyl glycidyl ether.
[0133] The viscosity is measured according to GB / T2794-2022 and is 2370 mpa.s. The non-volatile matter content is measured according to GB / T2793-1995 and is 23.55%.
[0134] Comparative Example 2:
[0135] The acrylic acid ester water-based adhesive was prepared in the same manner as in Example 1, except that:
[0136] The grafting monomer in step 5 is adjusted to ethylene glycol dodecyl ether.
[0137] The viscosity is measured according to GB / T2794-2022 and the non-volatile matter content is measured according to GB / T2793-1995 and is 23.46%.
[0138] Comparative Example 3:
[0139] The acrylic acid ester water-based adhesive was prepared in the same manner as in Example 1, except that:
[0140] In step 1, the only comonomer is acrylic acid.
[0141] Step 5 was modified to have no grafting monomer.
[0142] The viscosity was measured according to GB / T2794-2022 and was 2010 mpa.s. The non-volatile matter content was measured according to GB / T2793-1995 and was 23.0%.
[0143] Table 1, test results of embodiments and comparative examples:
[0144]
[0145] By comparing the examples and comparative examples, it is found that the water-based organic fluorine-modified acrylic adhesive obtained by the preparation method provided by the present invention has the following beneficial effects:
[0146] 1. There is no other solvent and emulsifier except pure water, which is more environmentally friendly;
[0147] Second, by grafting fluorinated monomers, the flexibility and dispersibility are improved; it is easier to get close to the PVDF surface, thereby improving the adhesion.
[0148] In order to streamline the present application and help understand one or more of the various application aspects, in the description of the exemplary embodiments of the present application, the various features of the present application are sometimes grouped together into a single embodiment, figure, or description thereof. However, the method of the present application should not be interpreted as reflecting the following intention: the claimed application requires more features than the features clearly stated in each claim. More specifically, as reflected in the corresponding claims, the application point is that the corresponding technical problem can be solved with less than all the features of a single disclosed embodiment. Therefore, the claims following the specific embodiment are hereby explicitly incorporated into the specific embodiment, wherein each claim itself serves as a separate embodiment of the present application.
[0149] In addition, those skilled in the art will appreciate that, although some embodiments described herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the claims, any one of the claimed embodiments can be used in any combination.
[0150] It should be noted that the above embodiments illustrate rather than limit the present application, and that those skilled in the art may design alternative embodiments without departing from the scope of the appended claims. In the claims, any reference symbol between brackets shall not be construed as a limitation to the claims.
Claims
1. A method for preparing an adhesive, characterized in that: In parts by weight, the preparation method comprises the following steps: Under nitrogen protection, 60-80 parts of pure water as solvent are added into the reactor; 0.1-0.3 parts of initiator and 5-15 parts of pure water are mixed to prepare solution A, and i types of comonomers are mixed to prepare solution B, where i≥1; The temperature of the reaction kettle is adjusted to 35-95° C., and the solution A and the solution B are dripped into the reaction kettle within 1-4 hours; After the solution A and the solution B are added dropwise, the reactor is kept warm. After 1-4 hours of warming, the temperature of the reactor is adjusted to 50-90° C., and 0-5 parts of fluorine-containing monomer are added to react; After adding the fluorine-containing monomer and reacting for 1-3 hours, the temperature of the reactor is adjusted to 35-65° C., 0.1-0.3 parts of a neutralizing agent are added, and after neutralization for 0.5-1 hour, the reaction mixture is cooled to obtain a water-based organic fluorine-modified acrylic adhesive.
2. The method for preparing an adhesive according to claim 1, characterized in that: The initiator is at least one of ammonium persulfate, potassium persulfate, sodium bisulfite, sodium hypophosphite, azobisisobutylimidazoline hydrochloride, and azobisisobutylamidine hydrochloride.
3. The method for preparing an adhesive according to claim 1, characterized in that: The comonomer is at least one of acrylic acid, methacrylic acid, itaconic acid, diethyl itaconate, acrylonitrile, methacrylonitrile, acrylamide and methacrylamide.
4. The method for preparing an adhesive according to claim 1, characterized in that: The structure of the fluorinated monomer is: Among them, 3≤n≤6, 6≤m≤8.
5. The method for preparing an adhesive according to claim 1, characterized in that: The neutralizing agent is at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide, calcium hydroxide, lithium carbonate, sodium carbonate, potassium carbonate, triethylamine, ammonia water, N,N-dialkylethanolamine, and N,N-dialkylhydroxylamine.
6. The method for preparing an adhesive according to claim 1, characterized in that: The step of dripping the solution A and the solution B into the reactor within 1-4 hours is specifically as follows: The solution A and the solution B are respectively dripped into the reaction kettle at a uniform speed within 1-4 hours.
7. The method for preparing an adhesive according to claim 1, characterized in that: The adhesive preparation method is specifically as follows: Under nitrogen protection, 70 parts of pure water were added into the reactor as a solvent; 0.15 parts of an initiator and 10 parts of pure water are mixed to form a solution A, wherein the initiator is ammonium persulfate; three comonomers are mixed to form a solution B, wherein the three comonomers include 18 parts of acrylic acid, 3 parts of acrylonitrile and 2 parts of acrylamide; After the temperature of the reactor reaches 90° C., the solution A is evenly dripped into the reactor within 3 hours, and the solution B is evenly dripped into the reactor within 2 hours; After the solution A and the solution B are added dropwise, the reactor is kept warm. After 2 hours of warming, the temperature of the reactor is adjusted to 70° C., and 1 portion of fluorinated monomer is added to react; After adding the fluorine-containing monomer and reacting for 2 hours, the temperature of the reactor was adjusted to 60° C., 0.2 parts of a neutralizing agent was added, and the neutralizing agent was sodium hydroxide. After neutralization for 0.5 hours, the mixture was cooled to obtain a water-based organic fluorine-modified acrylic adhesive.
8. The method for preparing an adhesive according to claim 1, characterized in that: The adhesive preparation method is specifically as follows: Under nitrogen protection, 70 parts of pure water were added into the reactor as a solvent; 0.15 parts of an initiator and 10 parts of pure water are mixed to form a solution A, wherein the initiator is ammonium persulfate; five comonomers are mixed to form a solution B, wherein the five comonomers include 15 parts of acrylic acid, 3 parts of acrylonitrile, 2 parts of acrylamide, 1 part of itaconic acid and 2 parts of diethyl itaconate; After the temperature of the reactor reaches 90° C., the solution A is evenly dripped into the reactor within 3 hours, and the solution B is evenly dripped into the reactor within 2 hours; After the solution A and the solution B are added dropwise, the reactor is kept warm. After 2 hours of warming, the temperature of the reactor is adjusted to 70° C., and 1 portion of fluorinated monomer is added to react; After adding the fluorine-containing monomer and reacting for 2 hours, the temperature of the reactor was adjusted to 60° C., 0.2 parts of a neutralizing agent was added, and the neutralizing agent was sodium hydroxide. After neutralization for 0.5 hours, the mixture was cooled to obtain a water-based organic fluorine-modified acrylic adhesive.
9. An adhesive, characterized in that: The adhesive is a water-based organic fluorine-modified acrylic adhesive prepared by the adhesive preparation method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The lithium ion battery comprises the adhesive of claim 9.